2007
DOI: 10.1002/jcb.21252
|View full text |Cite
|
Sign up to set email alerts
|

PAR1‐mediated RhoA activation facilitates CCL2‐induced chemotaxis in PC‐3 cells

Abstract: Patients with advanced prostate cancer often exhibit increased activation of the coagulation system. The key activator of the coagulation cascade is the serine protease thrombin which is capable of eliciting numerous cellular responses. We previously reported that the thrombin receptor PAR1 is overexpressed in prostate cancer. To investigate further the role of PAR1 in prostate cancer metastasis, we examined the effects of thrombin activation on cell adhesion and motility in PC-3 prostate cancer cells. Activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 25 publications
(27 reference statements)
1
27
1
Order By: Relevance
“…For example, Liu and colleagues have shown that thrombin increases DU145 adhesion to fibronectin and laminin via a mechanism involving PAR 1 (Liu et al, 2004). In contrast to DU145 cells, treatment of PC-3 cells with a similar concentration of thrombin and PAR 1 AP decreased cell adhesion to collagen I and IV and laminin and resulted in no change in adhesion to fibronectin (Loberg et al, 2007). In addition to cell migration and adhesion, examples of the co-opting of other normal cellular processes essential for cancer progression, such as tissue remodelling, cell growth, angiogenesis and mechanisms regulating apoptosis, have recently been shown to be mediated via PARs.…”
Section: Cancer-associated Consequences Of Par Activation In Prostatementioning
confidence: 77%
See 3 more Smart Citations
“…For example, Liu and colleagues have shown that thrombin increases DU145 adhesion to fibronectin and laminin via a mechanism involving PAR 1 (Liu et al, 2004). In contrast to DU145 cells, treatment of PC-3 cells with a similar concentration of thrombin and PAR 1 AP decreased cell adhesion to collagen I and IV and laminin and resulted in no change in adhesion to fibronectin (Loberg et al, 2007). In addition to cell migration and adhesion, examples of the co-opting of other normal cellular processes essential for cancer progression, such as tissue remodelling, cell growth, angiogenesis and mechanisms regulating apoptosis, have recently been shown to be mediated via PARs.…”
Section: Cancer-associated Consequences Of Par Activation In Prostatementioning
confidence: 77%
“…Consistently, PAR 1 and PAR 2 APs were able to initiate activation of the cytoskeleton reorganising GTPases RhoA, Rac1 and Cdc42 (Hall, 2005) in a manner similar to thrombin and trypsin in LNCaP cells (Greenberg et al, 2003). Loberg and colleagues have also shown that thrombin treatment of PC-3 cells causes retraction of the actin cytoskeleton and numerous microspike extensions from the cell body (Loberg et al, 2007). This treatment was accompanied by rapid activation of RhoA and Cdc42 with no change in the level of Rac-1 activation (Loberg et al, 2007).…”
Section: Cancer-associated Consequences Of Par Activation In Prostatementioning
confidence: 82%
See 2 more Smart Citations
“…CCL2 is a member of the CC subfamily of low molecular weight chemokines, a class of proteins that are essential in immune regulation, inflammation, and the healing response (7). Under aberrant pathological conditions, CCL2 has essential roles in the infiltration of tumor associated macrophages, which play a key role in increased tumorigenicity of PCa and other cancers (8). CCL2 acts as an autocrine and paracrine mitogenic and motogenic factor of the malignant human androgen-independent prostatic PC-3 cell line (6).…”
Section: Introductionmentioning
confidence: 99%